2009
DOI: 10.1002/bem.20526
|View full text |Cite
|
Sign up to set email alerts
|

No effects of mobile phone electromagnetic field on auditory brainstem response

Abstract: The present study investigated the possible effects of the electromagnetic field (EMF) emitted by an ordinary GSM mobile phone (902.4 MHz pulsed at 217 Hz) on brainstem auditory processing. Auditory brainstem responses (ABR) were recorded in 17 healthy young adults, without a mobile phone at baseline, and then with a mobile phone on the ear under EMF-off and EMF-on conditions. The amplitudes, latencies, and interwave intervals of the main ABR components (waves I, III, V) were compared among the three condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
1
7
1
2
Order By: Relevance
“…The retrosigmoid craniotomy directly exposes the eighth nerve to mobile phone EMF without any biological structure in between. This condition is clearly far from reproducing the real-life EMF absorption of neural structures, because it offers a reliable measurement of the direct effect of a known EMF on a sensitive nerve without the interposition of other structures (skin, skull, fat, muscle, blood, grey and white matter) that have different SAR 17 42. All these structures play an important role in determining the SAR of inner-ear structures in responses to EMF exposure 29…”
Section: Discussionmentioning
confidence: 99%
“…The retrosigmoid craniotomy directly exposes the eighth nerve to mobile phone EMF without any biological structure in between. This condition is clearly far from reproducing the real-life EMF absorption of neural structures, because it offers a reliable measurement of the direct effect of a known EMF on a sensitive nerve without the interposition of other structures (skin, skull, fat, muscle, blood, grey and white matter) that have different SAR 17 42. All these structures play an important role in determining the SAR of inner-ear structures in responses to EMF exposure 29…”
Section: Discussionmentioning
confidence: 99%
“…One early study by Kellényi et al [1999] reported a significant effect on ABR but they failed to replicate this finding [Stefanics et al, 2007]. The effects of mobile phone radiation with a weak transmission power could be transient, but only a few studies applied concurrent exposure during ABR measurements [Bąk et al, 2003;Sievert et al, 2005;Kwon et al, 2010b].…”
Section: Auditory Brainstem Responsementioning
confidence: 93%
“…The spatial average SAR in the user's head would be the maximum output divided by the mass of the head, but local peak values can be much higher depending on the distance to the phone and tissue type [Kwon et al, 2010b].…”
Section: Electromagnetic Fields Emitted By Mobile Phonesmentioning
confidence: 99%
“…A recent study concluded that short-term exposure to mobile phone EMFs did not affect the transmission of sensory stimuli from the cochlea up to the midbrain along the auditory nerve and the brainstem auditory pathways [21]. A study in Poland evaluated the ABRs in 45 young healthy volunteers before, during and after exposure to EMFs generated by antenna of a mobile phone.…”
Section: Discussionmentioning
confidence: 99%